DETERMINANTS OF INFLATION IN GCC COUNTRIES - Duha Alsheikh; Faisal Rana (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study aimed to determine the influence of GDP and money supply toward inflation level in GCC countries. The main data source was from World Data banks and regions indication lists. The World Bank data was extracted for relevant variables and countries. A linear regression model in simple terms was created by fitting line through construction of scatter plots of paired observations. The regression model was involved one variable plotted on x-axis and y-axis. The independent variables were GDP and money supply while dependent variable was inflation rate. The result showed money supply had impacted inflation which trend that was common for most countries. Thus, inflation indicators highlighted was confirmed as oil price. Besides, GDP was increased and caused inflation also increased in UAE which the economy was depended upon hydrocarbon as compared with other GCC countries